Betting on capital gains: housing speculation in Auckland, New Zealand. Issue 1 (27th April 2020) - Rehm, Michael; Yang, Yang
Abstract : Purpose: The purpose of this paper is to examine housing speculation in Auckland, New Zealand, the second most unaffordable market in the world. Design/methodology/approach: The study considers rental property purchases from 2002 to 2016 within the Auckland region. The authors apply a simple cash flow model that emulates the before-tax investment calculations used during purchasers' due diligence. From this model, the authors determine whether purchases involved speculation on capital gains or not and the authors estimate the degree of speculation at the transaction level. Findings: The authors find that housing speculation in Auckland is endemic and its housing market is a politically condoned, finance-fuelled casino with investors broadly betting on tax-free capital gains. Social implications: Although political leaders have decried that the "speculation-driven housing bubble in Auckland is a social and economic disaster", the government's main anti-speculation tool – the Income Tax Act's intention test – sits idle and inoperable. By holstering this key policy tool, politicians foster housing speculation and use residential property investment to buttress New Zealand's asset-based welfare system. Originality/value: The authors develop novel methods to objectively distinguish speculators from genuine investors, measure the speculative pressure applied by individual rental property purchasers and outline an evidence-based approach to operationalise New Zealand's currently impotent anti-speculation tool, the intention test.